Practical applications of in-vitro techniques to forage germplasm - Ruredzo, T.J.; Hanson, Jean (International Livestock Centre for Africa, 1990)
Reports the work in progress at ILCA on appropriate methods of collecting Digitaria species and multiplying these former species and Leucaena leucocephala, Erythrina brucei and Sesbania sesban in vitro. Discusses their potential use in forage genetic resources. Discusses inoculation of stem cuttings, incubation of cultures, rooting and transfer to soil. Presents results of collection, initiation and multiplication, slow growth conservation, adventitious regeneration and establishment in soil.